2015
DOI: 10.1002/gea.21534
|View full text |Cite
|
Sign up to set email alerts
|

The geology of the 2nd century A.D. Amphitheater Area of Catania, Italy: Historical Eruptions Affecting the Urban District

Abstract: The amphitheater of Catania is one of the main architectural structures built during Roman domination of the town. It was constructed in two successive phases between the 1st and 2nd centuries A.D. and fell into disuse from the second half of the 4th century. Detailed geological and petrographic investigations allow better geomorphological reconstruction of the area where the monument was built. In particular, the western and eastern portions of the amphitheater are built on prehistoric lava flows, named Barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other catalogs have since been published without substantial changes in the flank eruption records, but enhancing the scientific reconstruction of the past and recent activity from different perspectives (Andronico & Lodato, 2005;Behncke et al, 2005;Neri et al, 2011;Tanguy et al, 2007). More recently, Branca and Abate (2019) further detailed the historical catalog before the 18th century by a multidisciplinary approach comprising stratigraphy, historiographical studies, and geochronological dating of the lavas, that allowed defining a comprehensive assessment of the flank eruptions at Etna in the last 2500 years (Branca & Vigliotti, 2015;Branca et al, 2011Branca et al, , 2013Branca et al, , 2015bBranca et al, , 2016Tanguy et al, 2012).…”
Section: Overview and Applicationsmentioning
confidence: 99%
“…Other catalogs have since been published without substantial changes in the flank eruption records, but enhancing the scientific reconstruction of the past and recent activity from different perspectives (Andronico & Lodato, 2005;Behncke et al, 2005;Neri et al, 2011;Tanguy et al, 2007). More recently, Branca and Abate (2019) further detailed the historical catalog before the 18th century by a multidisciplinary approach comprising stratigraphy, historiographical studies, and geochronological dating of the lavas, that allowed defining a comprehensive assessment of the flank eruptions at Etna in the last 2500 years (Branca & Vigliotti, 2015;Branca et al, 2011Branca et al, , 2013Branca et al, , 2015bBranca et al, , 2016Tanguy et al, 2012).…”
Section: Overview and Applicationsmentioning
confidence: 99%
“…Ruins of ancient civilizations are often used as surface markers for Holocene tectonic and paleoseismic events (e.g., Ferrater, Silva, Orturio, Rodriguez‐Pascua, & Masana, ; Guidoboni, Comastri, Mariotti, Ciuccarelli, & Bianchi, ; Hinzen, Kehmeier, & Schreiber, ; Lin, Rao, Hu, & Gong, ; Marco et al., ; Silva et al., ) and time capsules for volcanic eruptions (e.g., Branca, Branciforti, Chiavetta, & Corsaro, ; Coltelli, Del Carlo, & Vezzeoli, ). Archaeoseismological studies have shown that repeated large earthquakes on active faults have caused extensive damage to ancient infrastructure and economies, as well as numerous deaths, in a variety of environments worldwide (e.g., Ferrater et al., ; Lin, Ren, Jia, & Miyairi, ; Lin et al., ; Rodriguez‐Pascua et al., ).…”
Section: Introductionmentioning
confidence: 99%